The effect of concrete composition and aggregates properties on performance of concrete - Mačiulaitis, Romualdas; Vaičienė, Marija; Žurauskienė, Ramunė (Journal of Civil Engineering and Management, 2009)
The properties of the hardened concrete depend on the selected raw materials: size and amount of the particles of coarse aggregate, as well as on the ratio of other components. Particular countries use various methodologies for the selection of concrete composition to select the components of the concrete mixture. However, the properties of the concrete, selected by using any methodology for the selection of the concrete composition and hardened by following the defined conditions, must satisfy the values of certain necessary characteristics. The results of the implemented research indicate that the most optimal solution is to use the coarse aggregate of multi‐fractional or discontinuous fractional composition. The optimal composition of the concrete must be selected to ensure that the binding material is not overdosed. Yet, all components must be selected in such a way, that the required properties of the final product are retained after concrete mixture hardens. When catalyst waste materials from the reactor of the catalytic cracking (15%) are used for the lightweight concrete, the density of the expanded‐clay lightweight concrete investigated and compressive strength increases even for the higher water/cement ratio, more heat is dissipated during the hydration of the cement and this exothermic effect occurs several hours earlier.SantraukaSukietėjusio betono savybės priklauso nuo betonui parinktų žaliavų: stambaus užpildo dalelių dydžio ir jų kiekio, taip pat nuo kitų sudedamųjų dalių santykio. Betono mišinio sudedamąsias dalis šalys parenka įvairiais betono sudėties parinkimo metodais, tačiau pagal bet kurį betono sudėties parinkimo metodą parinkto ir pagal nustatytas sąlygas sukietinto betono savybės turi tenkinti tam tikrų būtinųjų charakteristikų vertes. Darbe atliktų tyrimų rezultatai parodė, kad optimaliu naudoti daugiafrakcį arba trūkiosios frakcinės sudėties stambųjį užpildą. Betono sudėtis turi būti parinkta nepereikvojant rišamosios medžiagos, tačiau visas sudedamąsias dalis parenkant taip, kad, sukietėjus betono mišiniui, išliktų reikiamos galutinio produkto savybės. Lengviesiems betonams naudojant katalizatoriaus atlieką iš katalitinio krekingo reaktoriaus (15 %), padidėja tiriamojo keramzitbetonio tankis, gniuždomasis stipris net esant didesniam V/C santykiui, o hidratuojantis cementui, išsiskiria daugiau šilumos, ir šis egzoterminis efektas įvyksta keliomis valandomis anksčiau.First Published Online: 14 Oct 2010Reikšminiai žodžiai: betonas, užpildai, keramzitas, struktūriniai rodikliai, katalizatorius, egzotermijos temperatūra.